PERKEMBANGAN DAN DAMPAK PENGGUNAAN E-MONEY TERHADAP PERILAKU KONSUMTIF MASYARAKAT - Ayang Sukma (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2025)
The development of digital technology has driven a significant transformation in Indonesia's payment systems, notably through the use of e-money. The convenience and practicality offered by e-money have made it increasingly popular across various segments of society. However, alongside these benefits, concerns have emerged that uncontrolled usage may encourage consumptive behavior, particularly among the younger generation. This research aims to examine the relationship between the use of e-money and the tendency towards consumptive behavior through a literature review approach. Data sources were obtained from relevant scientific journals, official reports, and academic articles published within the last five to ten years. The findings indicate a positive correlation between the intensity of e-money usage and an increase in consumptive behavior. The ease of transactions, attractive promotions, and the absence of physical interaction with money are the primary factors driving this behavior. On the other hand, the levels of digital financial literacy and self-control are proven to mitigate the negative impacts of e-money usage. Therefore, collaborative efforts from the government, service providers, and educational institutions are necessary to raise public awareness about using e-money wisely. This research is expected to serve as a foundation for developing educational policies and for further studies related to consumer behavior in the digital era.